PERSEPSI ORANG TUA DALAM MENYEKOLAHKAN ANAKNYA KE SMP SWASTA NASIONAL - Aqiilah Dwi Oktavia; Budi Haryanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The objectives of this study include: [1] To determine parents' perceptions of National Private Junior High Schools; [2] To determine the extent to which parents' positive perceptions influence their decisions in choosing a school. The background of this study is based on the phenomenon of increasing public interest in private schools, even though public schools are still considered more prestigious and superior in terms of facilities and teaching staff. The method used in this study is qualitative with a positivistic approach, data was obtained through observation, in- depth interviews, and documentation of eight parents of students from various socio- economic backgrounds, as well as the school. The results of the study indicate that parents' perceptions of National Private Junior High Schools are very positive. The school is seen as having advantages in character building, instilling religious values, and a humanistic learning approach. Influencing factors, such as effective promotion, positive experiences from the surrounding community, teacher professionalism, affordable education costs, and a conducive school environment are the main considerations in decision making. Parents also observed positive developments in their children's self-confidence, religious habits, and social interactions after attending the institution. This study concludes that parents' perceptions play a significant role in children's educational decisions. The decision to send children to private junior high schools is not solely due to limited access to public schools, but rather based on confidence in the quality of education, the school's vision, and the values it instills. This study is expected to serve as a reference for educational institutions in improving service quality and building public trust.